2021
DOI: 10.1038/s41467-020-20224-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Mycobacterium tuberculosis CoaBC by targeting an allosteric site

Abstract: Coenzyme A (CoA) is a fundamental co-factor for all life, involved in numerous metabolic pathways and cellular processes, and its biosynthetic pathway has raised substantial interest as a drug target against multiple pathogens including Mycobacterium tuberculosis. The biosynthesis of CoA is performed in five steps, with the second and third steps being catalysed in the vast majority of prokaryotes, including M. tuberculosis, by a single bifunctional protein, CoaBC. Depletion of CoaBC was found to be bactericid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 57 publications
2
29
0
Order By: Relevance
“…To assess the mode of inhibition of CoaBC by 1f , competition experiments were carried out between the compound and the three substrates of CoaB (PPA, CTP, and l -cysteine) using the EnzChek coupled enzyme assay, as previously described. 41 We first confirmed that compound 1f was inactive on the coupled reporter enzymes at 100 μM. The IC 50 for this compound using the EnzChek assay was determined to be 24.3 μM against the Mtb CoaBC, comparable to that observed in the high-throughput screen ( Figure 3 a).…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…To assess the mode of inhibition of CoaBC by 1f , competition experiments were carried out between the compound and the three substrates of CoaB (PPA, CTP, and l -cysteine) using the EnzChek coupled enzyme assay, as previously described. 41 We first confirmed that compound 1f was inactive on the coupled reporter enzymes at 100 μM. The IC 50 for this compound using the EnzChek assay was determined to be 24.3 μM against the Mtb CoaBC, comparable to that observed in the high-throughput screen ( Figure 3 a).…”
Section: Resultssupporting
confidence: 61%
“…High-throughput screening of 215 000 small molecules from the DDU compound library was carried out to identify inhibitors of Mtb CoaB activity using an adaptation of the BIOLMOL Green end-point pyrophosphate quantification assay, as previously described. 41 This compound library predominantly comprises commercially available molecules representing a wide range of chemical space that possessing the favorable physicochemical and molecular properties required for a potential preclinical drug candidate, with a small subset of the library (<0.5%) comprising proprietary compounds with known phenotypic activity against a number of various pathogens. The primary screen, which had an overall hit rate of 0.6%, led to the identification of compound 1a , with an IC 50 of 9.9 μM against Mtb CoaB.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations